METHOD OF DETERMINING THE DYNAMICS OF INTERACTION LACTIC ACID BACTERIA IN THEIR JOINT CULTIVATION - V. V. Kondratenko; N. E. Posokina; O. Yu. Lyalina; A. Yu. Gracheva; Zh. A. Semenova; V. I. Tereshonok (Овощи России, 2018)
The processes of fermentation, accompanied by the growth and development of several species of microorganisms, are often accompanied by a change of some species of microorganisms for anothers , such a complex "behavior" of microorganisms during fermentation needs to be be deeply researched. The previously used approaches of evaluation of the type of interaction of particulate monocultures in consortiums make it possible to obtain only qualitative results (synergistic, antagonistic, additive interaction) generally, without taking into the consideration the change of this interaction during the cultivation. The purpose of the research was the development of a new approach of the quantitative determination of the parameter of the interaction of microorganisms of one species with another species expressed as a continuous function determined throughout the all fermentation period. In the process of the work a two-component consortium of lactic acid microorganisms Lactobacillus brevis and Lactobacillus plantarum was selected, cultivated in two different model media as part of a study of directed fermentation of vegetable products. The work the cultivation of monocultures (included in the studied consortium) was also carried out. The performed work the original approach was developed, the approach is based on a comparison of the growth rate of the microorganisms biomass of the consortium with the calculated additive dynamics. This approach is convenient to use to identify a complex regularity of changes of the types of interaction of microorganisms in the consortium in the form of a continuous function determined during the entire cultivation period. From the point of view of the synergies of the species of microorganisms entering the studied consortium in the active phase of fermentation, the "Slava" variety turned to be more profitable than the "Parus".